Architecture and Human Rights - Hossein Sadri (Journal of Contemporary Urban Affairs, 2019)
This article investigates on the concept of space, its production, use, and change processes, and uncovers the interrelations between social and spatial practices. Based on Lefebvre’s concept of the Right to the City, the article discussed two main spatial rights: the right to the oeuvre and the right to appropriation. To justify these spatial rights on the ground of legal rights, a comparison method is used in this article and three main legal documents is set against each other. These documents are the Universal Declaration of Human Rights, the ‘World Charter for the Right to the City’ and the ‘European Declaration of Urban Rights’. As a result of this comparison, 22 universal norms are identified. These norms and the awareness regarding them and their ethical and legal background can empower social/spatial activism and be used for performing and evaluating spatial practices.